2018
DOI: 10.1007/s40430-018-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

A study on mechanical behavior and wear performance of a metal–metal Co–30Cr biomedical alloy with different molybdenum addition and optimized using Taguchi experimental design

Abstract: Molybdenum-added biomedical alloy has been prepared using a high-temperature vertical vacuum casting technique with five (0, 1, 2, 3, and 4 wt%) diverse weight percentages. The density, microhardness, and sliding wear behavior of the fabricated alloys were studied, showing that the addition of molybdenum content in the metal-metal alloy (i.e., Co-30Cr) increases the density from 7.2 to 8.7 g/cc for 0-4 wt% of Mo, respectively. Similarly, the hardness of prepared biomedical alloy also increases from 653 to 720 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These nano-bioceramic composites have revolutionized the subjectmatter of nanocomposites materials for hip implants, and related biomedical industry. Many authors have reported and evaluated problems related to friction and wear of different (polymer, metal, and ceramic) available implants materials [6][7][8][9][10][11][12][13][14][15]. The fundamental objective of studying tribological facets and performance of any material is to reduce or minimize the material loss or to reduce the damage to even zero especially when to be used as implants inside human body where this material loss is intolerable.…”
Section: Introductionmentioning
confidence: 99%
“…These nano-bioceramic composites have revolutionized the subjectmatter of nanocomposites materials for hip implants, and related biomedical industry. Many authors have reported and evaluated problems related to friction and wear of different (polymer, metal, and ceramic) available implants materials [6][7][8][9][10][11][12][13][14][15]. The fundamental objective of studying tribological facets and performance of any material is to reduce or minimize the material loss or to reduce the damage to even zero especially when to be used as implants inside human body where this material loss is intolerable.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that interconnectivity and porosity are essential to promote cell culture, tissue growth, loading and migration of cells, tissue growth, and flow of body fluid [10][11][12][13]. At present, a number of researchers [5,6,[14][15][16][17][18][19][20][21] are working with non-conventional techniques and state-of-the-art fused deposition modeling (FDM) is one of them. This technique has been becoming most popular in biomedical field owing to its high flexibility of producing different shaped implants, 3D faxing, and green manufacturing nature.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the major problem faced by scientist in the field of implant material is the selection of appropriate constituent materials with the accurate weight percentage and design of composition for optimized physical, mechanical and tribological properties. Metallic implants are the prime implant materials utilized for femoral component and are becoming increasingly important [1][2][3][4][5]. The metallic implants utilized for orthopaedic applications can be classified as stainless steel, cobalt-chrome alloys and titanium alloys [6,7].…”
Section: Introductionmentioning
confidence: 99%